Challenges and opportunities under COVID-19 on rural populace in Kailash Sacred Landscape (KSL)-India - Ravindra K. Joshi; Ravi Pathak; Rishav Rawal; Shinny Thakur; Vikram S. Negi; I.D. Bhatt (Environmental Challenges, 2022)
More than just a health crisis, COVID-19 pandemic has stressed across social, economical and emotional dimensions of human well being and health. The sudden enforcement although willful and honest, perpetuated a sense of insecurity and uncertainty as a result of livelihood loss, especially for the people employed in unorganized and private sectors across different urban centers of the country. The unexpected scenario not only caused widespread joblessness but also created varied conditions of psychological stresses foreseeing the less likelihood of returning of pre-COVID conditions. As an outcome of the pandemic, the involuntarily return of youth was seen as a boon for reversing the undesirable and unprecedented trends impacting the traditional rural dynamics. Present study is an attempt to highlights impacts, challenges and opportunities under and after COVID-19 on rural populace of Kailash Sacred Landscape (KSL) amid the sudden halt of remittances and jobless aspiring youth. A systematic approach was followed, where 16 villages in eight Blocks of KSL were assessed and migrants (n=815) were interviewed for compiling the information. Results revealed that COVID-19 has impacted (both positively and negatively) various sectors such as agriculture, tourism, overall family income, etc., as perceived by the respondents. Sectors like restaurants/shops, tourism, and agriculture emerged as potential cash generating avenues, with 30 %, 21 %, and 20 % respondent's perception, respectively. It is also revealed that in the absence of immediate alternatives, and policy intervention, villagers engaged themselves in the time tested traditional sectors of livelihoods or created their own niche by integrating traditional wisdom and acquired skills.